2022
DOI: 10.3390/plants11131781
|View full text |Cite
|
Sign up to set email alerts
|

Response Mechanisms of “Hass” Avocado to Sequential 1–methylcyclopropene Applications at Different Maturity Stages during Cold Storage

Abstract: 1–Methylcyclopropene (1–MCP) is used for extending the postharvest life of the avocado during storage. Evaluated the effect of 1–MCP application at different times after harvest, i.e., 0, 7, 14, and 21 d at 5 °C, to identify the threshold of the ethylene inhibition response in “Hass” avocado. Our results showed that fruits from two maturity stages at harvest: low dry matter (20–23%) and high dry matter (27%). Changes in ethylene production rates and transcript accumulation of genes involved in ethylene metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…After 30 days of storage at 5 °C, twice as much ethylene was found in the RA-stored fruits than in the fruits stored under a CA ( Figure 1 A). The increase in ethylene production in fruits stored under RA conditions could be due to an advanced ripening process, which was consistent with the findings of our previous study [ 9 , 24 ], and occurred because RA technology cannot delay the ripening process; however, CA can delay the onset of climacteric ethylene production [ 18 ]. Other cultivars stored under RA or CA, such as ‘Edranol’ and ‘Fuerte’, exhibited similar patterns of ethylene production [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…After 30 days of storage at 5 °C, twice as much ethylene was found in the RA-stored fruits than in the fruits stored under a CA ( Figure 1 A). The increase in ethylene production in fruits stored under RA conditions could be due to an advanced ripening process, which was consistent with the findings of our previous study [ 9 , 24 ], and occurred because RA technology cannot delay the ripening process; however, CA can delay the onset of climacteric ethylene production [ 18 ]. Other cultivars stored under RA or CA, such as ‘Edranol’ and ‘Fuerte’, exhibited similar patterns of ethylene production [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…After 30 days of cold storage, the parameter value decreased (near 200 N). Similar effects were reported by Olivares et al [ 9 , 18 ] and Alamar et al [ 19 ], in which RA-stored fruit softened rapidly for 35 days at 5 °C (3–4 days to reach the RTE stage). Furthermore, Burdon et al [ 20 ], reported that CA-stored fruit ripened more slowly than RA-stored fruit.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations